3D stratigraphic forward numerical modelling approach for prediction of organic-rich deposits and their heterogeneities. (April 2017) - Bruneau, Benjamin; Chauveau, Benoit; Baudin, François; Moretti, Isabelle
Abstract: The source rock characteristics (e.g. thickness, lateral extension, richness) are known to be highly variable in both time and space. The Lower Jurassic formations of north-western Europe contain source rocks with organic-rich intervals showing different characteristics from one region to another: the Paris Basin differs from the South-East Basin of France, but organic content and hydrogen index also vary within a single basin. During the Early Jurassic, the overall depositional environment of north-western Europe corresponded to an epicontinental domain at the western extremity of the Tethys Ocean. The early transgressive phase of the Jurassic induced flooding of this European realm. Because of the evolution of the connections and threshold of the European basins and their associated sedimentary settings, this domain occupied a key position for the deposition of organic-rich layers. Using a forward modelling approach, we aim to predict the heterogeneous characteristics of such sediments. It is widely accepted that primary productivity and preservation are key factors favouring the accumulation of organic-rich layers. However, the roles of these factors remain to be assessed and the processes leading to accumulation and preservation need to be quantified. We focus on the Lower Jurassic (Hettangian to Toarcian) in France, since this provides a vast amount of data to calibrate the 100-kyr time step model in terms of an accurate framework including paleogeography, stratigraphy, lithology, palaeontology, mineralogy and geochemistry. Results show that favourable conditions for the deposition of organic-rich sediment can occur even with moderate primary productivity and without requiring anoxic conditions. These windows are firstly dependent on internal factors directly linked to the basin morphology, such as sedimentation rate, bathymetry and distance from the coastline. We do not need to evoke external factors such as oceanic anoxic events or enhancement of primary production to account for the deposition of organic-rich sediments. Highlights: First 3D process-oriented model of organic matter in Lower Jurassic European basins. Influence of paleogeography and slope geometry on the source rock characteristics. Organic matter distribution/heterogeneity processes are identified and quantified.